Design, Synthesis, and Antifungal Activity of Some Novel Phenylthiazole Derivatives Containing an Acylhydrazone Moiety - Yao Tian; Jinchao Shi; Xiaoqian Deng; Tingyu Yu; Yong Hu; Richa Hu; Yufeng Lei; Linhua Yu; Xiang Zhu; Junkai Li (Molecules, 2023)
Crop fungal diseases pose a serious threat to global crop production and quality. Developing new and efficient fungicides is an important measure to control crop diseases. Phenylthiazole was found to be an excellent antifungal skeleton based on our previous study on the structural optimization and biological activity of the natural product thiasporine A. To find new fungicides, 45 phenylthiazole derivatives containing an acylhydrazone moiety were designed and synthesized by the principle of active substructure splicing. Forty-two of the forty-five compounds are novel, except for compounds E1, E14, and E33. Their structures were structurally characterized by 1H NMR, 13C NMR, and HRMS. The antifungal activities of the target compounds against Magnaporthe oryzae Colletotrichum camelliaet, Bipolaris maydis, and Sclerotinia sclerotiorum were evaluated at 25 μg/mL. The bioassay results revealed that most of these compounds exhibited excellent antifungal activities against M. oryzae and C. camelliaet at 25 μg/mL. In particular, compounds E4, E10, E14, E17, E23, E26, and E27 showed the inhibition rate of more than 80% against M. oryzae, with EC50 values of 1.66, 2.01, 2.26, 1.45, 1.50, 1.29, and 2.65 μg/mL, respectively, which were superior to that of the commercial fungicides Isoprothiolane (EC50 = 3.22 μg/mL) and Phenazine-1-carboxylic acid (EC50 = 27.87 μg/mL). The preliminary structure–activity relationship (SAR) results suggested that introducing methyl, halogen, or methoxy at the ortho-position of R1 and the para-position of R2 can endow the final structure with excellent antifungal activity against M. oryzae. The current results provide useful data for developing phenylthiazole derivatives as new fungicides for controlling rice blast caused by M. oryzae.